Criminological ideas and the South African transition - Zyl Smit, Dirk van (The British journal of criminology, 1999)
The struggles surrounding apartheid and the quest for democracy have had an important impact on the development of criminological thought in South Africa. This paper describes the three major tendencies in South African criminological thought: the formerly dominant Afrikaner nationalist criminology, legal reformism and a critical criminology with a commitment to democratic and communitarian practice. It traces the opportunities for development that the immediate transition to democracy offered to the latter two tendencies in particular. It then sketches the extent to which the ideals of the various tendencies have been met since the first democratic election in 1994 and outlines the obstacles to their implementation that have emerged. In conclusion, the paper considers the prognoses for the various tendencies and warns that, notwithstanding the undoubted achievements of South African critical criminology, an undiscriminating reliance on the communitarian ideals of the transition may make it difficult for the South African criminal justice system to meet the challenges it now faces